Examination timetable scheduling system (ETSS) / Fong Teng Heng - Fong, Teng Heng (2000)
This documentation IS about the development of Examination Timetable Scheduling System or can be called ETSS. ETSS is to develop a university examination timetable that ensures not only that there will not be any clashes but also several constraints are satisfied, e.g. the seating capacity of exam hall should match as for as possible the number of students in the hall. The algorithm using can be referred to Graph colouring. ETSS uses Visual Basic 6.0 as a programming language. The database is stored in Access 97.